Exploring profiles of anxiety symptoms in male and female children on the autism spectrum. (August 2020) - Ambrose, Kathryn; Adams, Dawn; Simpson, Kate; Keen, Deb
Highlights: Previous research has been inconclusive regarding anxiety profiles in male and female children on the autism spectrum. Findings of this study show that overall male and female children on the autism spectrum had similar anxiety symptoms. Sex differences were detected on the Anxious Arousal subscale scores only. Anxiety in children on the autism spectrum warrants further investigation. Abstract: Background: It is now recognised that children on the autism spectrum frequently experience co-occurring anxiety. Although a child's sex is thought to impact the prevalence of anxiety in typically developing children, the relationship between sex and anxiety symptoms has not previously been established in children on the autism spectrum. This study compares the parent-reported anxiety symptoms of male and female children (aged 9–12 years) on the autism spectrum. Method: 24 male and 24 female children with a diagnosis of autism spectrum disorder were matched on age, VABS receptive language scores, and SCQ scores. Anxiety was measured using the ASC-ASD-P, a 24-item questionnaire designed to capture typical and atypical signs of anxiety in children on the autism spectrum. A combination of descriptive and inferential analyses was used to compare the total anxiety scores, anxiety subscale scores, and anxiety item scores of males and females. Results: No significant differences were found between the total anxiety scores of males and females, or the performance anxiety, separation anxiety, or uncertainty subscale scores. Females had significantly higher anxiety scores on the anxious arousal subscale which was due to significant differences on two individual anxiety items within that subscale. Conclusion: Overall, male and female children on the autism spectrum, aged 9–12 years, had similar anxiety scores. The profiles of anxiety in male and female children on the autism spectrum may differ from those reported in typically developing children and warrant further investigation.